Albania : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Review Under Extended Arrangement, and Financing Assurances Review. (IMF Staff Country Reports; Country Report, 2007)
This paper discusses key findings of the Second Review Under the Poverty Reduction and Growth Facility for Albania. The outlook for 2007 is positive, with growth projected at 6 percent. These developments owe much to good macroeconomic policies. All quantitative program targets were met. The 2007 budget is in line with the medium-term fiscal framework, which strikes a balance between reducing public debt and increasing priority expenditure. Progress in structural reform has been generally good. The program focuses on reducing fiscal vulnerabilities, improving budget management, and developing the financial system.